Pengaruh Metode Continuous Running Terhadap Peningktan Daya Tahan Siswa Ekstrakurikuler Pencak Silat di Pondok Pesantren Modern Nurussalam - Muhammad Fajriyudin; Rizki Aminudin; Fahrudin Fahrudin (Jurnal Literasi Olahraga, 2021)
This research was motivated by the lack of endurance of the pencak silat extracurricular students at the Modern Nurussalam Islamic Boarding School. This type of research is a quantitative study, which is to determine the effect of the Continuous Running method on the enhancement of the endurance of the pencak silat extracurricular students at the Modern Nurussalam Islamic Boarding School. The method used in this research is experimental. Pretest post research design. The research subjects were 14 students of the extracurricular pencak silat at the Modern Nurussalam Islamic Boarding School. In this study, there are 2 variables. Namely, independent variables: Continuous Running Method, and dependent variable: Endurance of Nurussalam pencak silat extracurricular activities. The instrument used in this study was the Bleep Test. From the results of the research the effect of the Continuous Running Method on the VO2max of the Pencak Silat Extracurricular Students at the Modern Nurussalam Islamic Boarding School. The following are the results of research conducted by extracurricular Pencak Silat students at the Modern Nurussalam Islamic Boarding School and the following results were obtained: mean (mean), standard deviation (SD), and VO2max from each of the lowest pre-test data 23.6 and the highest was 30.6 and the lowest post test was 27.2 and the highest was 38.5. Then the average (mean) pre test of endurance ability was 26.19, and the post test was 32.72. The standard deviation (SD) of pre test is 1.88, and post test is 2.96. Change (D) of 6.54.